Analisis Elemen Visual Pada Desain Kemasan Makanan Ringan Nyam Nyam Bubble Puff - Mufida, Iklima Nur; Sishertanto, Tytton (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
Packaging plays an important role in product usage within the production industry. Its function has evolved into a brand value creation tool, particularly for snack packaging products. This has attracted the author's attention to study the packaging of Nyam Nyam Bubble Puff snacks, chosen for their enduring popularity among child consumers. This research employs a descriptive qualitative method based on design theory. The analysis focuses on the visual graphic elements of Nyam Nyam Bubble Puff snack packaging that can influence consumer decision-making. The visual elements analyzed include logo or brand, color, illustration, shape, layout, and typography. The proper and effective selection of design elements in packaging can attract potential consumers to purchase products, as seen with Nyam Nyam Bubble Puff snacks. This research is expected to assist manufacturers producing new products in applying a creative and strategic packaging design approach to increase consumer interest further.